Linguistic Analysis of Gokana Personal Names (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The purpose of this research was to do an analysis on Gokana Personal names, an area of Onomastics called Anthroponomy. These names were analyzed linguistically. To achieve this, three native speakers of Gokana were interviewed as language consultants and ninety names were collected. A morphological analysis was done on some of these names and the morphological processes identified were affixation and compounding. Simple word names were also identified. From the analysis, the researchers also found out that some names were sentential. It was also discovered that Gokana names are made up of one, two, three and even four syllables according to the data under study. A socio-semantic analysis was also done on the names, were the meanings attached to these names were looked at.